Some legal problems arising in the maritime commerce between France and the African states - (:unkn) unknown (My University, 1983)
This paper endeavours to identify some legal problems which recently have arisen in the maritime commerce between France and the African states.Such commerce, however on the whole satisfactory, has encountered a first problem, arising from the diversity of applicable legal régimes, and the difficulty of choosing the appropriate one among them. Since 1960 many African states have enacted their own maritime laws, without adhering to the 1924 Brussels international convention on the maritime carriage of goods, the so called Hague Rules. Also, States which have adhered to the 1924 Convention have not adhered to the 1968 Brussels Protocol modifying the Convention, and adhered to by France. Thus, it is almost impossible, without costly litigation, to ascertain the very legal status of a given contract of maritime carriage between France and an African state, such status varying according to the court before which the case is brought. And the choice of law has important consequences. In case of transportation of the heavy goods, the amount of compensation accorded to the consignee, if the goods are damaged, may vary from 1 to 100, or even more.The only means to eliminate any uncertainty will be, for the African states, to adhere to the Hamburg Rules of 1978, more especially as such rules are favourable to them.Another problem, arising in cases of transportation of large volume of goods spread out along a long period of time, is the problem of choice between a contract of affreightment and a contract of carriage. Very recently, many cases have arisen before French courts or arbitrators, concerning long term contracts for carriage of bananas or other tropical fruits, as such contracts did not make clear which kind of contract, carriage or affreightment, the parties intended to conclude. Here, however, the solution is an easy one: to make precise and beyond doubt the choice which has been made.A last problem more and more frequently arises, when goods have to b
Keywords: African Research